2018
DOI: 10.1016/j.bbi.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hypothermia and delayed mesenchymal stem cell therapy in neonatal hypoxic-ischemic brain injury

Abstract: Acute hypothermia treatment (HT) is the only clinically established intervention following neonatal hypoxic-ischemic brain injury. However, almost half of all cooled infants still die or suffer from long-lasting neurological impairments. Regenerative therapies, such as mesenchymal stem cells (MSC) appear promising as adjuvant therapy. In the present study, we hypothesized that HT combined with delayed MSC therapy results in augmented protection, improving long-term neurological outcome. Postnatal day 9 (P9) C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 32 publications
2
82
0
1
Order By: Relevance
“…MSCs have gained much interest in the therapy for various disorders and have also shown augmented protection in the treatment of neonatal hypoxic-ischemic brain injury [35]. Recently, exosomes derived from MSCs have been found to carry various kinds of mediators, miRNAs and proteins, which can mediate the function of MSCs [10,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have gained much interest in the therapy for various disorders and have also shown augmented protection in the treatment of neonatal hypoxic-ischemic brain injury [35]. Recently, exosomes derived from MSCs have been found to carry various kinds of mediators, miRNAs and proteins, which can mediate the function of MSCs [10,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…There is concerning evidence that in P9 mice combined therapy with hypothermia and mesenchymal stem cells after hypoxia‐ischaemia was less protective than either alone (Herz et al . ), illustrating the high importance of formally testing combined effects. Overall, these findings strongly suggest overlapping protective mechanisms of rEpo and therapeutic hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bone marrow derived mesenchymal stem cells treatment after hypoxic injury in neonatal murine model promoted neuronal and oligodendrocyte regeneration (van Velthoven et al, 2010). Mesenchymal stem cell therapy in combination with hypothermia resulted in reduced hypoxia induced hypomyelination and memory deficits in neonatal C57BL/6 mice (Herz et al, 2018). Intraperitoneal injection of human cord blood derived mesenchymal stem cells in neonatal rats increased the count of mature oligodendrocytes and reduced the number of reactive astrocytes as well as reactive microglia, ameliorating the hypoxia induced brain damage (Zhu et al, 2014).…”
Section: Attenuation Of Myelination Deficitsmentioning
confidence: 99%